DEVELOPMENT CAPACITY AND SYNERGY OF REGIONAL AUTHORITIES IN EARLY DETECTION OF TERRORISM ACTIONS - Yudi Rusfiana; Abu Hanifah (Jurnal Ilmiah Wahana Bhakti Praja, 2021)
Terrorism that occurs in Indonesia is inseparable from a series of global terrorism, early detection must be carried out through capacity building and synergy of regional officials who have intelligence functions both within the TNI, Poliri and local governments. Optimization of the capacity and synergy of these officials can be carried out through the Government, including local governments, to synergize early detection through various means, especially by taking actions in accordance with applicable legal procedures. The government, through related officials, has made approaches through community leaders, moderate religious figures and those who tend to be radical in order to change radical thinking to moderate, namely by providing a true understanding of the term jihad. From the said capacity building and synergy, it is hoped that acts of terrorism can always be anticipated. Key words: Early detection, Territorial Apparatus, Terrorism